Putting Power Back Into Growth Theory - Blair Fix (Review of Capital as Power, 2015)
Neoclassical growth theory assumes that economic growth is an atomistic process in which changes in distribution play no role. Unfortunately, when this assumption is tested against real-world evidence, it is systematically violated. This paper argues that a reality-based growth theory must reject neoclassical principles in favour of a powercentered approach. Building on Nitzan and Bichler's Capital as Power hypothesis, I argue that hierarchy formation is an integral part of the growth process. I hypothesize that the role of capital accumulation (through profit) is to facilitate hierarchy formation by legitimizing the authority of capitalists.
Keywords: 330; economic growth theory; distribution; power; hierarchy; energy